A comparative analysis of the effectiveness of learning English vocabulary between smart device and printed material. (1st January 2014) - Jo, Jaechoon; Lim, Heuiseok
A high level of vocabulary comprehension affects the learning process for the English language. There are contemporary ways to learn English vocabulary through academic environments and media lectures from the internet. One in particular, smart learning, which is the method of learning using smart devices. Recently, this new method of learning a new language has been receiving recognitions from learners around the world. This study is a comparative analysis for the learning effects of smart learning that are based on a lexical decision task. Two groups were made: a group that used smart devices and a group that used in-classroom material, such as textbooks. These two kinds of methods are useful tools for the learning effects of the students. Although both groups had positive outcomes, learning effects with a neuro-scientific base can be further raised when applied to the new methods of smart devices rather than the traditional methods using textbooks.